PENGELOLAAN ARSIP DALAM MENINGKATKAN LAYANAN PADA DINAS ARSIP DAN PERPUSTAKAAN KABUPATEN SUMEDANG - Karlina, Neneng Rita (LPPM UNSAP & FISIP UNSAP, 2025)
This study aims to determine the Management of Archives in Improving Services at the Archives and Library Service of Sumedang Regency. The background of this study is based on the ongoing problems related to the facilities and infrastructure for managing archives, as well as adequate development for employees in improving their abilities and competencies. The research method used in this study is a qualitative approach with a descriptive research type. Determination of samples/informants in this study was carried out using purposive sampling, namely 4 people consisting of the Head of the General Sub-Section, Head of Archives, Archivist Functional Staff 1 and Archivist Functional Staff 2. Data collection techniques were carried out through literature studies and field studies through (observation, interviews and documentation) and triangulation. After that, data processing used data collection, data reduction, data presentation and verification. The results of the study indicate that the implementation of Archives Management in Improving Services at the Archives and Library Service of Sumedang Regency has been running, but has not been optimal. In general, archive management refers to Law Number 43 of 2009 concerning Archives and Guidelines for the Management of Archives Units at State Institutions Number 20 of 2012 from the National Archives of the Republic of Indonesia with a clear work program. However, there are still obstacles such as lack of facilities and infrastructure, budget limitations, and the archive depot space is far from the office location of the Sumedang Regency Archives and Library Service. On the other hand, this management has provided benefits in the form of increased knowledge and awareness to each Regional Apparatus Organization (OPD) of the importance of archives. This study suggests that the Sumedang Regency Archives and Library Service can further intensify socialization, counseling, and technical assistance activities to all Regional Apparatus Organizations (OPD) evenly and sustainably so that awareness and ability to manage archives according to national standards increase as a whole.